Efektivitas Terapi Murottal Al-Quran Terhadap Kecemasan Anak Dengan Leukemia “Literature Review” - Ricky Zainuddin; Rahma La Maru ((JKG) Jurnal Keperawatan Global, 2019)
Background: Murottal therapy is a type of music therapy that has a positive influence on the listener, when someone listens to murottal therapy it will give stimulation to the eardrum then it will begin the listening process where every sound produced by the sound source will be passed through the auditory nerve to the auditory cortex in the brain. Then murottal therapy will work on the brain where when given a stimulus the brain will produce a decrease in cortisol so that it can provide feedback in the form of relaxed feeling and comfort. Methods: This research explores quantitative evidence published in pubmed electronic databases, google scholar. By using search strategy we found 73 articles with the potential of 10 studies included in the final analysis. Results: We found a significant post-intervention improvement in reducing anxiety for participants who received murottal Al-Qur’an therapy compared to all control grups. Conclusion: These results indicate that murottal Al-Qur'an therapy can be used as an alternative treatment to reduce anxiety of patients who experience anxiety disorders and nurses are expected to participate in this treatment training.